The applicability of using a protease extracted from cashew fruits (Anacardium occidentale), as possible meat tenderizer: an experimental design approach - Ahmad, Mohammad Norazmi; Shuhaimen, Muhammad Shahrain; Abdullah, Erna Normaya; Omar, Muhammad Nor; Iqbal, Anwar; Ku Bulat, Ku Halim (Blackwell Publishing Ltd, 2020)
Meat tenderness is one of the most important organoleptic properties in determining consumer acceptance in meat product marketability. Therefore, an effective meat tenderization method is sought after by exploring plant derived proteolytic enzymes as meat tenderizer. In this study, a novel protease from Cashew was identified as a new alternative halal meat tenderizer. The extraction of cashew protease was optimized using response surface methodology (R2 = 0.9803) by varying pH, CaCl2 concentration, mixing time, and mass. pH 6.34, 7.92 mM CaCl2 concentration, 5.51 min mixing time, and 19.24 g sample mass were the optimal extraction conditions. There was no significant difference (n = 3; p < 0.05) between the calculated (6.302 units/ml) and experimental (6.493 ± 0.229 units/ml) protease activity. The ascending order of the effects was pH < mixing time < CaCl2 < sample mass. In meat tenderizing application, the meat samples treated with 9% (v/w) crude protease extract obtained the lowest shear force (1.38 ± 0.25 N) to cause deformation on the meat. An electrophoretic analysis showed that protein bands above 49.8 kDa were completely degraded into protein bands below 22.4 kDa. Scanning electron microscopy shows the disruption of the muscle fibers after being treated by the Cashew protease. The results of this study show the Cashew (Anacardium occidentale) crude extract can be used as an alternative of the animal and microbial protease as meat tenderizer and subsequently overcome the shortcoming of the halal industrial protease.